2021
DOI: 10.1108/gm-07-2020-0231
|View full text |Cite
|
Sign up to set email alerts
|

Psychological capital and entrepreneurship: gender differences

Abstract: Purpose This study aims to examine whether the psychological capital of male and female university students explains the intention to undertake entrepreneurism. Following Ajzen’s theory of planned behaviour, the aim was to study whether perceived behavioural control and subjective norms influence entrepreneurial intention and if subjective norms moderate established relationships, in both genders. Design/methodology/approach Structural equation modelling and analysis of variance was applied to test the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 61 publications
4
28
0
2
Order By: Relevance
“…Another interesting finding concerns the work-home conflict (Thébaud, 2015; Ahl, 2006) and the need for a support network (corroborating findings of Kim et al , 2020 and Villanueva-Flores et al , 2021). The interviewees stated that they had work–home conflicts only during specific times (COVID-19 or high demand periods), but all five respondents reported having relied on spousal support.…”
Section: Cross Case Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Another interesting finding concerns the work-home conflict (Thébaud, 2015; Ahl, 2006) and the need for a support network (corroborating findings of Kim et al , 2020 and Villanueva-Flores et al , 2021). The interviewees stated that they had work–home conflicts only during specific times (COVID-19 or high demand periods), but all five respondents reported having relied on spousal support.…”
Section: Cross Case Discussionmentioning
confidence: 54%
“…This scenario has changed considerably in the past few decades, however. With over 252 million female entrepreneurs worldwide (GEM, 2019), albeit accounting for less than 10% of the related research (Brush and Cooper, 2012) – most studies use gender only as a control variable (Villanueva-Flores et al , 2021) – entrepreneurship research runs the risk of having a one-sided empirical focus (Gatewood et al , 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, previous studies have reported interesting sociodemographic correlates of life satisfaction, psychological capital, and positive organizational practices. Namely, some studies indicated a significant effect of gender and age on life satisfaction [144,145], some significant effect of gender on psychological capital [146][147][148], and just some significant effect of age on psychological capital [149]. However, the role of age and gender on positive organizational practices has not been fully explored, even though previous research provided some results on the effects of age on positive organizational practices [21].…”
Section: Importance Of the Studymentioning
confidence: 99%
“…Accordingly, during this challenging time of the pandemic, this study was primarily focused on positive aspects in different sectors and aimed to identify positive organizational practices, life satisfaction, and psychological capital of the public sector employees and compare the results with the scores of the private sector employees. As some studies indicated the possible effect of gender and age-related variables [144,[146][147][148], we considered it essential to explore their role, as it might provide some additional information for a better understanding of the underlying mechanisms.…”
Section: Importance Of the Studymentioning
confidence: 99%